Implementasi Model Pembelajaran Discovery Learning Pada Mata Pembelajaran Pendidikan Agama Islam - Putri, Giska Amelia; Muliati, Indah; Saputra, Edi (An-Nuha, 2023)
Discovery Learning is a method of understanding concepts, meanings and relationships, through an intuitive process to finally arrive at a conclusion. This Discovery Learning model is able to have a positive influence on the activity of students, the ability to think critically, and the results during the learning process of students. Based on the problems above, the teacher plays an important role in the learning process. This discovery model can make the class atmosphere more active, not boring and the most important thing is that it can stimulate students to think critically. Therefore, it is necessary to do research to find out how to plan, implement and evaluate the learning of Islamic Religious Education based on the Discovery Learning Model in SMPN 7 Sijunjung. This research method is qualitative with a descriptive research type. With this data collected is not in the form of numbers but from the results of observations and interviews. The informants in this study were curriculum representatives, Islamic Religious Education teachers, and SMPN 7 Sijunjung students. The techniques used in analyzing the data are data reduction, presentation and conclusions. The planning stage carried out by the PAI teacher is by making a Learning Plan. The implementation of the Discovery model goes according to the steps applied to the implementation, where there are 3 learning stages, namely preliminary activities, core activities and closing. The evaluation that is used when using the discovery model is that the teacher measures it by conducting tests both orally and in writing and also the teacher also often collaborates with the reflection stage on students using games.